ℵ1-directed inverse systems of continuous images of arcs - Ivan Lončar (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is to prove that if X={Xa,pab,A} is a usual ℵ1-directed inverse system of continuous images of arcs with monotone bonding mappings, then X=limX is a continuous image of an arc (Theorem 2.4). Some applications of this statement are also given.